2022
DOI: 10.1021/acs.biomac.2c00143
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Amino Acid-Derived Polyacrylates as Smart Materials Exhibiting Cellular Specificity and Therapeutic Activity

Abstract: The synthesis of new amino acid-containing, cell-specific, therapeutically active polymers is presented. Amino acids served as starting material for the preparation of tailored polymers with different amino acids in the side chain. The reversible addition–fragmentation chain-transfer (RAFT) polymerization of acrylate monomers yielded polymers of narrow size distribution (Đ ≤ 1.3). In particular, glutamate (Glu)-functionalized, zwitterionic polymers revealed a high degree of cytocompatibility and cellular speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
(100 reference statements)
0
18
1
Order By: Relevance
“…The chemical structure of the side chain in pGlnMA was the same as that of a reported glutamine-functionalized pLys, which was also internalized into BxPC3 via recognition by ASCT2. The cellular uptake behavior of pGlnMA-CCP in the present study might be similar; however, BzlSer has the potential to bind to other AATs; therefore, more detailed experiments are required to determine if this is an ASCT2-specific interaction.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The chemical structure of the side chain in pGlnMA was the same as that of a reported glutamine-functionalized pLys, which was also internalized into BxPC3 via recognition by ASCT2. The cellular uptake behavior of pGlnMA-CCP in the present study might be similar; however, BzlSer has the potential to bind to other AATs; therefore, more detailed experiments are required to determine if this is an ASCT2-specific interaction.…”
Section: Resultsmentioning
confidence: 79%
“…A strong affinity of glutaminecontaining polymers for cancer cells expressing ASCT2 has been reported, although the AATs on cancer cells that recognize these polymers are still under discussion. 20,28 ASCT2 is overexpressed on various types of cancer cells, such as CT26 29 and 4T1 cells. 30 For the expression level of on CT26 and 4T1 cells by Western blotting, it was observed that CT26 cells expressed ASCT2 1.2 times as high as 4T1 cells (Figure S14).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The labeling efficiency was analyzed using UV–vis spectroscopy and calculated by the determination of the molar concentration of dye relative to the molar concentration of polymer (λ max = 646 nm, ε = 230,400 M –1 cm –1 ). All polymers showed a similar incorporation of Cy5, which was determined to be 3–4 dyes per polymer chain (Table ) and which was a particularly critical parameter to use for accurate comparisons in subsequent cell studies . With a focus on different shape/size effect on cell interactions, small-angle neutron scattering (SANS) was further used to analyze the size and shape of the polymeric nanoparticles.…”
Section: Resultsmentioning
confidence: 99%